The role of self-help groups in post-tsunami rehabilitation. (September 2015) - Larson, Grant; Drolet, Julie; Samuel, Miriam
This article provides an analysis of the importance of self-help groups for women in post-tsunami rehabilitation efforts in Tamil Nadu, India. The finding is one of eight key themes identified in a larger study of the long-term social, economic and gender implications of post-tsunami rehabilitation work. While self-help groups were reported as having provided women with a measure of new social and economic opportunities, status and power, little evidence existed for a substantial reduction of poverty levels or a change in the prevailing patriarchal attitudes. The authors suggest that multiple long-term sustainable approaches to post-disaster reconstruction are needed to provide fundamental social and economic change for women.